Assessment of the capacity of local actors for disaster resilient coastal tourism development the case of the municipality of Baler in Aurora - Kalaw, Jose Cipriano A.; Napalang, Ma. Sheilah Gaabucayan (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
The Municipality of Baler in the province of Aurora in the Philippines is becoming one of the most popular coastal tourism destinations in the country, known for its beach and surfing activities. The coastal tourism industry has become a primary source of employment, investment and local economic growth for Baler. But coastal areas, especially those in the Philippines, are exposed to natural hazards that pose a threat to lives, properties and the long term sustainability of the industry. It is imperative therefore to strengthen the disaster resilience of these destinations. The study asserts that local actors must comprehend disaster risk; have resources available; and commit to implementing programs and interventions towards integrating disaster risk reduction and management in coastal tourism development. Among the strengths of the local actors of Baler is the high level of awareness of DRMM, particularly, of the policies and guidelines on Disaster Risk Reduction and Management, natural hazards and risks, and the interventions necessary to strengthen disaster resilience. Overall, the local actors in Baler's coastal tourism industry have done well in cooperating and utilizing a truly whole-of-society approach that is consultative and participatory towards building disaster resilient coastal tourism development. Baler can therefore become a resource for other local governments and developers to understanding how disaster resilience can be mainstreamed into coastal tourism development.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Coastal zone management -- Philippines -- Baler (Aurora).; Ecotourism -- Philippines -- Baler (Aurora).; Emergency management -- Philippines -- Baler (Aurora).